DETERMINAN SUKU BUNGA PASAR UANG ANTAR BANK TAHUN 1990-2019 - Juan Patrick Lie (2022)
The Interbank Money Market Interest Rate is the interest rate used in banking and determined by the central bank used for transactions on the money market in Indonesia. Interbank money market interest rates are influenced by various monetary factors such as inflation, exchange rates, money supply and investment. This study aims to determine the effect of inflation, exchange rates, money supply and investment on interbank money market interest rates. This study uses data from 1990-2019 per year. The method used in this study is a multiple linear analysis model using the OLS method. The results of multiple linear regression analysis show that (1) there is a significant effect between inflation and interbank money market interest rates (2) there is a significant effect between exchange rates and interbank money market interest rates (3) there is a significant effect between the amount of money circulating with interbank money market interest rates (4) there is a significant effect between investment and interbank money market interest rates.